Pengembangan E-Book Interaktif Pembelajaran Kolaboratif Menggunakan Teknologi Cloud Computing pada Mata Kuliah PPDP PPG Prajabatan - Hariswan Putera Jaya; Dedi Kurniawan; Abdul Gafur; Nurbuana Nurbuana; Apriyanti Apriyanti; Ermalati Putri; Miftahunajah Aditiya Pratama (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to develop an interactive e-book for the course "Understanding Learners and Their Learning" with a collaborative learning approach based on cloud computing technology for students in the Pre-Service Teacher Professional Program (PPG) Prajabatan. The research method used is developmental research consisting of three stages: preliminary research, prototype stage, and assessment stage, with a focus on the utilization of cloud computing technology. Data were collected through questionnaires, validity tests, and the effectiveness of the interactive e-book developed through stages designed according to the Akker model. Data analysis was conducted quantitatively and qualitatively. Formative evaluation was carried out to determine the validity, practicality, and potential effects of the product. The validity of the developed e-book reached a score of 3.55 (very high validity) after evaluation by experts in the context of learning design, media, and content. The practicality of the e-book was rated high in one-on-one evaluation (score 3.625) and very high in small group evaluation (score 3.85). Field tests showed an effectiveness rate of 94.4%, indicating that the interactive e-book has high potential effects. This e-book can be implemented effectively for Prajabatan PPG students as a reference source supporting the understanding of learners and learning through a collaborative approach based on cloud computing technology.